2019
DOI: 10.1016/j.heliyon.2019.e02232
|View full text |Cite
|
Sign up to set email alerts
|

Simple crystallization approach for enhancing function of plant-based madder dye and performance of dyed fabric

Abstract: In the present study, the natural madder dye was investigated to the simultaneous extraction and dyeing of cotton (natural fiber) and nylon (synthetic fiber). The optimum dye extraction conditions were found to be 80 °C, 60 min, and 1:6 with ethyl alcohol after madder had been fermenting for 24 hours with water as solvent. Interestingly, crystallization can be done to separate crystal mollugin from dyed solution. And then, dyed fabrics exhibited improved color strength and ultraviolet protection factor. Meanwh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…where R is the observed reflectance, K is the absorption coefficient, and S is the light scattering coefficient. In general, the greater the K/S value, the deeper the color on the fabric [34,35].…”
Section: Color Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…where R is the observed reflectance, K is the absorption coefficient, and S is the light scattering coefficient. In general, the greater the K/S value, the deeper the color on the fabric [34,35].…”
Section: Color Measurementsmentioning
confidence: 99%
“…A renewed international interest has arisen Nanomaterials 2022, 12, 3953 2 of 11 in natural dyes as they are among the promising options for developing a greener textile dyeing process [29,30]. Natural plant dyes applied to textile dyeing have been reported to confer a variety of health benefits and functionalities on textiles, such as UV protection, antibacterial activity, deodorization, anti-carcinogenicity, and anti-oxygenation [31][32][33][34]. However, due to the low affinity between the colorants and the fibers when natural dyes are used in textile dyeing, they cannot be well fixed on the fibers, resulting in poor color fastness of the dyed fabrics [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, from Table 7, the anti-UV property of the undyed cotton treated only with mordant was not different from that of raw cotton fabric, which showed that the Al 3+ in the alum mordant had no property of UV resistance. 36…”
Section: Wearing Analysis Of Cotton Fabricmentioning
confidence: 99%
“…Crystal engineering, as an important part of supramolecular chemistry, deals with the understanding of intermolecular interactions in the context of crystal packing and the utilization of such understanding in the design of new solids with expected physiochemical properties, which has been widely used in academia and industry, including pharmaceuticals, chemicals, photographic processing, textiles, electronics, etc. With the exploitation of crystal engineering strategies, recent decades have witnessed an enormous interest in the design of multicomponent crystalline materials (e.g.…”
Section: Introductionmentioning
confidence: 99%